Heterogeneous Microtesla SABRE Enhancement of 15N NMR Signals. (28th July 2017) - Kovtunov, Kirill V.; Kovtunova, Larisa M.; Gemeinhardt, Max E.; Bukhtiyarov, Andrey V.; Gesiorski, Jonathan; Bukhtiyarov, Valerii I.; Chekmenev, Eduard Y.; Koptyug, Igor V.; Goodson, Boyd M.
Abstract: The hyperpolarization of heteronuclei via signal amplification by reversible exchange (SABRE) was investigated under conditions of heterogeneous catalysis and microtesla magnetic fields. Immobilization of [IrCl(COD)(IMes)], [IMes=1, 3‐bis(2, 4, 6‐trimethylphenyl), imidazole‐2‐ylidene; COD=cyclooctadiene] catalyst onto silica particles modified with amine linkers engenders an effective heterogeneous SABRE (HET‐SABRE) catalyst that was used to demonstrate a circa 100‐fold enhancement of 15 N NMR signals in 15 N‐pyridine at 9.4 T following parahydrogen bubbling within a magnetic shield. No 15 N NMR enhancement was observed from the supernatant liquid following catalyst separation, which along with XPS characterization supports the fact that the effects result from SABRE under heterogeneous catalytic conditions. The technique can be developed further for producing catalyst‐free agents via SABRE with hyperpolarized heteronuclear spins, and thus is promising for biomedical NMR and MRI applications.